Pengaruh Fasilitas Ruang Tunggu Keberangkatan terhadap Kepuasan Penumpang Di PT Angkasa Pura I Cabang Bandar Udara Internasional El Tari-Kupang, Nusa Tenggara Timur - Fransiska, Teresia; Astutik, Septiyani Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In this study, the authors took a case or problem regarding whether there is an influence of departure waiting room facilities on passenger satisfaction at PT Angkasa Pura I El Tari International Airport Branch Kupang, how much influence the departure waiting room facilities have on passenger satisfaction at PT Angkasa Pura I El Tari International Airport Branch Kupang, East Nusa Tenggara. The sample in this study were 100 passenger respondents who had used the services of El Tari Kupang International Airport. The type of research used in this study is quantitative, data collection techniques are carried out by distributing questionnaires and literature studies. Based on the results of hypothesis testing, the significance value of the coefficient table obtained a Sig. deviation from linearity value of 0.615>0.005 and based on the t value, it is known that t count is 11.313> t table of 1.660, meaning that there is an influence between variable X (departure lounge facilities) on variable Y (passenger satisfaction). So it can be concluded that Ho is rejected and Ha is accepted. There is an influence between departure waiting room facilities on passenger satisfaction at El Tari Kupang International Airport. The effect of departure waiting room facilities on passenger satisfaction at El Tari Kupang International Airport is 56.6%. Keywords : facilities, departure waiting room, passenger satisfaction.